1984
DOI: 10.1037/0012-1649.20.4.568
|View full text |Cite
|
Sign up to set email alerts
|

Developmental changes in hemispheric specialization for tactual processing in very young children: Evidence from cross-modal transfer.

Abstract: This experiment was conducted to determine whether young children show any evidence of right hemispheric specialization for tactual processing. Seventy-two 1-, 2-, and 3-year-old right-handed children were each administered six cross-modal tasks in which they palpated a shape with either their left or right hand for 25 s and then viewed the familiar and a novel shape in a 10-s test of visual recognition. Although children of all three ages showed significantly more visual fixation to novel shapes, regardless o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
14
2

Year Published

1988
1988
2015
2015

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 31 publications
(47 reference statements)
6
14
2
Order By: Relevance
“…In fact, infants as young as 2 months of age show the ability to retain haptic information better when that information is exposed to the left hand than when exposed to the right hand ( Lhote and Streri, 1998 ). This result in infants aligns with other studies in early childhood that reported that 2-year-olds display an advantage for visually recognizing novel geometrical shapes that were previously haptically manipulated with the left (but not the right) hand ( Rose, 1984 ). This left-hand advantage for novel object recognition has also been reported in older children (6–12 year olds; Witelson, 1974 , 1976 ).…”
Section: Sensory Contributions To Hand Preference For Reaching and Grsupporting
confidence: 90%
“…In fact, infants as young as 2 months of age show the ability to retain haptic information better when that information is exposed to the left hand than when exposed to the right hand ( Lhote and Streri, 1998 ). This result in infants aligns with other studies in early childhood that reported that 2-year-olds display an advantage for visually recognizing novel geometrical shapes that were previously haptically manipulated with the left (but not the right) hand ( Rose, 1984 ). This left-hand advantage for novel object recognition has also been reported in older children (6–12 year olds; Witelson, 1974 , 1976 ).…”
Section: Sensory Contributions To Hand Preference For Reaching and Grsupporting
confidence: 90%
“…For example, the dichotomy of visually guided reaching versus manipulative behavior for the left and right hands, respectively, would be difficult to maintain had the authors incorporated the findings of Ettlinger and colleagues in which a left hand preference was observed in monkeys for haptic perception involving manipulative behavior (see target article, Footnote #1). This left-hand haptic preference is not dissimilar to that observed for right-handed children as young as 2-years-old, who showed more accurate perception of objects palpated with the left hand, than with the right, which is considered to be a manifestation of right-hemisphere specialization for form perception (Rose 1984). The findings of Ettlinger and colleagues, and the results of the other studies of hand preferences in nonhuman primates, are all consistent with right-hemisphere specialization in monkeys for aspects of form and space perception, with the left-hand preference for the activities that draw on these processes being a result, or a reflection, of the contralateral hemisphere's functional specialization.…”
Section: Hand Preference: Basis or Reflection Of Hemisphere Specializcontrasting
confidence: 51%
“…An infant's handedness status, by ensuring differences in haptic experience between the two hands, can contribute to the establishment of differences in the processes of sensorimotor control and patterns of perceptual-motor organization between the two hemispheres (Michel, 1988). These asymmetrical differences between the hemispheres may account for the differences between the hands both in patterns of tactual exploration of objects and in sensitivity to differences in tactile stimuli among children as young as 2 years (Rose, 1984). Thus, it is conceivable that a hand-use preference will have a significant impact on how infants manage the possession and exploration of multiple objects.…”
Section: Introductionmentioning
confidence: 93%